PO 56 - AVALIAÇÃO DA SATISFAÇÃO DOS PAIS NO BLOCO OPERATÓRIO PEDIÁTRICO - Gonçalves, Ana Rita; Duarte, Sónia; Pina, Pedro; Machado, Humberto (Journal of the Portuguese Society of Anesthesiology, 2023)
x